A NEW VERSION OF ENERGY FOR SLANT HELIX WITH BENDING ENERGY IN THE LIE GROUPS - Körpınar, Talat (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2017)
In this work, we research geometrical interpretation involved with the energy on Lie groups. We explore the geometric properties of spherical graphics by way of energy. We apply totally diverse discussion and approach to illustrate bending energy functional for slant helix. Moreover, we have an original and satisfactorily association among energy of the curve in Lie groups.
Keywords: Energy; Slant Helix; Lie Groups; Vector Fields; Bending Energy